Discovery of fluorescent coumarin-benzo[b]thiophene 1, 1-dioxide conjugates as mitochondria-targeting antitumor STAT3 inhibitors - Cai, Guiping; Yu, Wenying; Song, Dongmei; Zhang, Wenda; Guo, Jianpeng; Zhu, Jiawen; Ren, Yuhao; Kong, Lingyi (European journal of medicinal chemistry, 2019)
STAT3 has been extensively studied as a potential antitumor target. Though studies on regulating STAT3 mainly focus on the inhibition of STAT3 phosphorylation at Tyr705 residue, the phosphorylation at Ser727 residue of STAT3 protein is also closely associated with the mitochondrial import of STAT3 protein. N, N-diethyl-7-aminocoumarin is a fluorescent mitochondria-targeting probe. In this study, a series of STAT3 inhibitors were developed by connecting N, N-diethyl-7-aminocoumarin fluorophore with benzo [b]thiophene 1, 1-dioxide moiety. All designed compounds displayed potent anti-proliferative activity against cancer cells. The representative compound 7a was mainly accumulated in mitochondria visualized by its fluorescence. STAT3 phosphorylation was inhibited by compound 7a at both Tyr705 and Ser727 residues. Compound 7a inhibited STAT3 phosphorylation whereas had no influence on the phosphorylation levels of STAT1, JAK2, Src and Erk1/2, indicating good selectivity of compound 7a. Moreover, compound 7a down-regulated the expression of STAT3 target genes Bcl-2 and Cyclin D1, increased ROS production and remarkably reduced the mitochondrial membrane potential to induce mitochondrial apoptotic pathway. Furthermore, compound 7ain vivo suppressed breast cancer 4T1 implanted tumor growth. Taken together, these results highlighted that compound 7a might be a promising mitochondria-targeting STAT3 inhibitor for cancer therapy. Compound 7a acted as a mitochondria-targeting STAT3 inhibitor to exert antitumor activities in vitro and in vivo. [Display omitted] •Fluorescent coumarin-BTP conjugates were discovered as mitochondria-targeting STAT3 inhibitors.•Compound 7a was mainly accumulated in mitochondria.•Compound 7a inhibited STAT3 phosphorylation at both Tyr705 and Ser727 residues.•Compound 7a exhibited potent antitumor activity in vitro.•Compound 7a arrested tumor growth in vivo.